Impact of type of oral anticoagulants in patients with cerebral microbleeds after atrial fibrillation-related ischemic stroke or TIA: Results of the NOACISP-LONGTERM registry - Wagner, Benjamin; Hert, Lisa; Polymeris, Alexandros A.; Schaedelin, Sabine; Lieb, Johanna M.; Seiffge, David J.; Traenka, Christopher; Thilemann, Sebastian; Fladt, Joachim; Altersberger, Valerian L.; Zietz, Annaelle; Dittrich, Tolga D.; et al. (Frontiers in neurology, 2022)
Cerebral microbleeds (CMBs) may have a differential impact on clinical outcome in stroke patients with atrial fibrillation (AF) treated with different types of oral anticoagulation (OAC).BackgroundCerebral microbleeds (CMBs) may have a differential impact on clinical outcome in stroke patients with atrial fibrillation (AF) treated with different types of oral anticoagulation (OAC).Observational single-center study on AF-stroke-patients treated with OAC. Magnetic-resonance-imaging was performed to assess CMBs. Outcome measures consisted of recurrent ischemic stroke (IS), intracranial hemorrhage (ICH), death, and their combined analysis. Functional disability was assessed by mRS. Using adjusted logistic regression and Cox proportional-hazards models, we assessed the association of the presence of CMBs and OAC type (vitamin K antagonists [VKAs] vs. direct oral anticoagulants [DOACs]) with clinical outcome.MethodsObservational single-center study on AF-stroke-patients treated with OAC. Magnetic-resonance-imaging was performed to assess CMBs. Outcome measures consisted of recurrent ischemic stroke (IS), intracranial hemorrhage (ICH), death, and their combined analysis. Functional disability was assessed by mRS. Using adjusted logistic regression and Cox proportional-hazards models, we assessed the association of the presence of CMBs and OAC type (vitamin K antagonists [VKAs] vs. direct oral anticoagulants [DOACs]) with clinical outcome.Of 310 AF-stroke patients treated with OAC [DOACs: n = 234 (75%); VKAs: n = 76 (25%)], CMBs were present in 86 (28%) patients; of these, 66 (77%) received DOACs. In both groups, CMBs were associated with an increased risk for the composite outcome: VKAs: HR 3.654 [1.614; 8.277]; p = 0.002; DOACs: HR 2.230 [1.233; 4.034]; p = 0.008. Patients with CMBs had ~50% higher absolute rates of the composite outcome compared to the overall cohort, with a comparable ratio between treatment groups [VKAs 13/20(65%) vs. DOACs 19/66(29%); p < 0.01]. The VKA-group had a 2-fold higher IS [VKAs:4 (20%) vs. DOACs:6 (9%); p = 0.35] and a 10-fold higher ICH rate [VKAs: 3 (15%) vs. DOACs: 1 (1.5%); p = 0.038]. No significant interaction was observed between type of OAC and presence of CMBs. DOAC-patients showed a significantly better functional outcome (OR 0.40 [0.17; 0.94]; p = 0.04).ResultsOf 310 AF-stroke patients treated with OAC [DOACs: n = 234 (75%); VKAs: n = 76 (25%)], CMBs were present in 86 (28%) patients; of these, 66 (77%) received DOACs. In both groups, CMBs were associated with an increased risk for the composite outcome: VKAs: HR 3.654 [1.614; 8.277]; p = 0.002; DOACs: HR 2.230 [1.233; 4.034]; p = 0.008. Patients with CMBs had ~50% higher absolute rates of the composite outcome compared to the overall cohort, with a comparable ratio between treatment groups [VKAs 13/20(65%) vs. DOACs 19/66(29%); p < 0.01]. The VKA-group had a 2-fold higher IS [VKAs:4 (20%) vs. DOACs:6 (9%); p = 0.35] and a 10-fold higher ICH rate [VKAs: 3 (15%) vs. DOACs: 1 (1.5%); p = 0.038]. No significant interaction was observed between type of OAC and presence of CMBs. DOAC-patients showed a significantly better functional outcome (OR 0.40 [0.17; 0.94]; p = 0.04).In AF-stroke patients treated with OAC, the presence of CMBs was associated with an unfavorable composite outcome for both VKAs and DOACs, with a higher risk for recurrent IS than for ICH. Strokes were numerically higher under VKAs and increased in the presence of CMBs.ConclusionsIn AF-stroke patients treated with OAC, the presence of CMBs was associated with an unfavorable composite outcome for both VKAs and DOACs, with a higher risk for recurrent IS than for ICH. Strokes were numerically higher under VKAs and increased in the presence of CMBs.http://www.clinicaltrials.gov, Unique identifier: NCT03826927.Clinical trial registrationhttp://www.clinicaltrials.gov, Unique identifier: NCT03826927.